'ADVANCE' (a pilot trial) ADjuVANt chemotherapy in the elderly: Developing and evaluating lower-toxicity chemotherapy options for older patients with breast cancer. Issue 1 (January 2023) - Freedman, Rachel A.; Li, Tianyu; Sedrak, Mina S.; Hopkins, Judith O.; Tayob, Nabihah; Faggen, Meredith G.; Sinclair, Natalie F.; Chen, Wendy Y.; Parsons, Heather A.; Mayer, Erica L.; Lange, Paulina B.; Basta, Ameer S.; et al.
Abstract: Introduction: Older adults with breast cancer receiving neo/adjuvant chemotherapy are at high risk for poor outcomes and are underrepresented in clinical trials. The ADVANCE (AD juVAN t C hemotherapy in the E lderly) trial evaluated the feasibility of two neo/adjuvant chemotherapy regimens in parallel-enrolling cohorts of older patients with human epidermal growth factor receptor 2-negative breast cancer: cohort 1—triple-negative; cohort 2—hormone receptor-positive. Materials and Methods: Adults age ≥ 70 years with stage I-III breast cancer warranting neo/adjuvant chemotherapy were enrolled. Cohort 1 received weekly carboplatin (area under the curve 2) and weekly paclitaxel 80 mg/m 2 for twelve weeks; cohort 2 received weekly paclitaxel 80 mg/m 2 plus every-three-weekly cyclophosphamide 600 mg/m 2 over twelve weeks. The primary study endpoint was feasibility, defined as ≥80% of patients receiving ≥80% of intended weeks/doses of therapy. All dose modifications were applied per clinician discretion. Results: Forty women ( n = 20 per cohort) were enrolled from March 25, 2019 through August 3, 2020 from three centers; 45% and 35% of patients in cohorts 1 and 2 were age > 75, respectively. Neither cohort achieved targeted thresholds for feasibility. In cohort 1, eight (40.0%) met feasibility (95% confidence interval [CI] = 19.1–63.9%), while ten (50.0%) met feasibility in cohort 2 (95% CI = 27.2–72.8). Neutropenia was the most common grade 3–4 toxicity (cohort 1—65%, cohort 2—55%). In cohort 1, 80% and 85% required ≥1 dose holds of carboplatin and/or paclitaxel, respectively. In cohort 2, 10% required dose hold(s) for cyclophosphamide and/or 65% for paclitaxel. Discussion: In this pragmatic pilot examining chemotherapy regimens in older adults with breast cancer, neither regimen met target goals for feasibility. Developing efficacious and tolerable regimens for older patients with breast cancer who need chemotherapy remains an important goal. ClinicalTrials.gov Identifier: NCT03858322.